2011
DOI: 10.3201/eid1705.101334
|View full text |Cite
|
Sign up to set email alerts
|

Babesiosis in Lower Hudson Valley, New York, USA

Abstract: Cases were associated with tick bites and receipt of blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 17 publications
(24 reference statements)
1
59
0
5
Order By: Relevance
“…In the lower Hudson Valley region of NYS, five locally acquired cases of babesiosis were reported in 2001 (Kogut et al 2005). The incidence had increased 20-fold from 2001 through 2008 ( Joseph et al 2011). We detected B. microti DNA in 6% (n = 25/628 pools) of samples tested.…”
Section: Babesia Microtimentioning
confidence: 79%
“…In the lower Hudson Valley region of NYS, five locally acquired cases of babesiosis were reported in 2001 (Kogut et al 2005). The incidence had increased 20-fold from 2001 through 2008 ( Joseph et al 2011). We detected B. microti DNA in 6% (n = 25/628 pools) of samples tested.…”
Section: Babesia Microtimentioning
confidence: 79%
“…Another limitation of our study is that we made no attempt to assess whether our patients may have been coinfected with babesiosis (18). This omission probably had minimal impact on our findings, however, since babesiosis did not occur in our geographic area of New York until 2001 (19,20).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we developed a multiplex real-time PCR assay for detection of B. microti DNA in blood samples. The diagnostic value of this assay was validated in patients from the Lower Hudson Valley region of New York State where I. scapularis transmitted diseases are highly endemic (Aliota et al, 2014;Hersh et al, 2014;Joseph et al, 2011;Kogut et al, 2005). It is estimated that 3-7% of I. scapularis ticks in this area are infected with B. microti (Aliota et al, 2014;Hersh et al, 2014;Kogut et al, 2005), while the highest incidence of human babesiosis has been reported in residents of three counties in the Lower Hudson Valley east of the Hudson River (6.6-25.1 cases per 100,000 population in 2013) (NYSDOH, 2014).…”
Section: Introductionmentioning
confidence: 99%